MOOD STATE, MOTIVATION AND IMPULSIVENESS AMONG STUDENTS PARTICIPATING IN YOUTH SCHOOL GAMES - Karla Medeiros Costa; Eduardo Penna; Humberto Luis de Deus Inácio; Claudio Andre Barbosa de Lira; Gustavo De Conti Teixeira Costa (Journal of Physical Education)
ABSTRACT The objective of the present study was to describe the mood state, motivation and impulsiveness of students participating in youth school games and to compare these variables between sexes. The research was cross-sectional, and the sample was composed of 147 students aged 12 to 17 years old (14.53±1.51 years; 51.70% of male participants). The following scales were used: 1) Brunel Mood Scale; 2) Motives for Physical Activity Measure - Revised, and 3) Impulsive Behavior Scale. For comparison between groups, the Mann-Whitney U test was used, and the effect size was calculated by means of Cohen’s d. The results showed that female students presented higher scores for anxiety, anger, confusion, depression, fatigue, lack of perseverance and premeditation. On the other hand, male students presented higher scores for appearance and health, seeming to be more motivated by extrinsic factors compared to females. Therefore, it is suggested that training strategies should be adapted by sex, in view of the respective characteristics.